1999
DOI: 10.1042/0264-6021:3440391
|View full text |Cite
|
Sign up to set email alerts
|

A processing intermediate of a stromal chloroplast import protein in Chlamydomonas

Abstract: Proteins synthesized in the cytoplasm and destined for importation into the chloroplast across the double envelope membrane contain an N-terminal transit sequence which upon import is cleaved off by a stromal-processing peptidase. Since for stromal-residing proteins no intermediates have ever been found in vivo, it is assumed that precursor proteins are cleaved to the mature size by one proteolytic event which occurs immediately after translocation across both envelope membranes. During import of the precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Both proteins were thermolysin resistant and therefore located within the chloroplast. iSS had been localized to the intermembrane space of the envelope [32].…”
Section: Resultsmentioning
confidence: 99%
“…Both proteins were thermolysin resistant and therefore located within the chloroplast. iSS had been localized to the intermembrane space of the envelope [32].…”
Section: Resultsmentioning
confidence: 99%
“…By fractionation of such chloroplasts into supernatant and membranes, SS and iSS were found to be soluble proteins while pSS remained bound to the membrane fraction. Furthermore, treatment of chloroplasts after pSS import both with thermolysin, which degrades proteins outside the outer envelope membrane, and with trypsin, acting additionally in the intermembrane space, revealed that iSS but not SS was located in the intermembrane space of the chloroplast envelope [14]. These findings raised the question about the physiological role of iSS and the enzyme SPP-1.…”
Section: Introductionmentioning
confidence: 99%
“…In itro, a stromal protein fraction enriched in SPP-2 cleaved pSS (20.6 kDa) at the N-terminal side of Met-46 (processing site 2), thereby producing the ' mature ' protein small subunit (SS ; 16.3 kDa), whereas SPP-1 cleaved pSS N-terminally of Met-25 in the middle of the pre-sequence (processing site 1), producing the intermediate-sized form iSS (18.3 kDa) [13]. iSS could also be detected after import of heavily labelled pSS into isolated chloroplasts [14]. By fractionation of such chloroplasts into supernatant and membranes, SS and iSS were found to be soluble proteins while pSS remained bound to the membrane fraction.…”
Section: Introductionmentioning
confidence: 99%
“…were subsequently modified by coevolution with the respective receptor associated with that translocon. This might explain the modular structure of transit peptides in plants (Bruce, 2000) and previous results indicating that the N-terminal part of the SSU protein leader peptide in Chlamydomonas is processed to an intermediate form in the envelope intermembrane space upon import into chloroplasts (Su et al, 1999).…”
Section: Evolution Of a Targeting System For Plastids With Two Membranesmentioning
confidence: 72%